2020
DOI: 10.3390/ijerph17165828
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Preconception Exposure to Air Pollution and Greenness with Offspring Asthma and Hay Fever

Abstract: We investigated if greenness and air pollution exposure in parents’ childhood affect offspring asthma and hay fever, and if effects were mediated through parental asthma, pregnancy greenness/pollution exposure, and offspring exposure. We analysed 1106 parents with 1949 offspring (mean age 35 and 6) from the Respiratory Health in Northern Europe, Spain and Australia (RHINESSA) generation study. Mean particulate matter (PM2.5 and PM10), nitrogen dioxide (NO2), black carbon (BC), ozone (O3) (µg/m3) and greenness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 46 publications
1
26
0
Order By: Relevance
“…Furthermore, a recent analysis found higher asthma risk in offspring if mothers had been exposed to air pollution before age 18 years. 20 A role of preconception occupational exposure through the paternal line was suggested in an analysis of fathers' exposure to welding and metal fumes, showing increased asthma related to preconception exposure but no effect of postnatal exposure. 18 Indirect support to a role of preconception occupational exposure in childhood asthma is provided by a Swedish registry study that found that several occupations, in which the employees most likely would have been exposed to cleaning agents, were associated with an increased risk of hospitalization for childhood asthma in offspring.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, a recent analysis found higher asthma risk in offspring if mothers had been exposed to air pollution before age 18 years. 20 A role of preconception occupational exposure through the paternal line was suggested in an analysis of fathers' exposure to welding and metal fumes, showing increased asthma related to preconception exposure but no effect of postnatal exposure. 18 Indirect support to a role of preconception occupational exposure in childhood asthma is provided by a Swedish registry study that found that several occupations, in which the employees most likely would have been exposed to cleaning agents, were associated with an increased risk of hospitalization for childhood asthma in offspring.…”
Section: Discussionmentioning
confidence: 99%
“…26 Emerging evidence from animal and human studies supports that environmental and occupational exposures might cause epigenetic changes that might be transmissible to offspring. [14][15][16][17][18][19][20][21][22]39 Such environmentally induced epigenetic alterations must be present in the germline to be transmissible to the next generation. 13,24 Alterations passed through the germline might result in inherited changes in gene expression in offspring in any kind of tissue and hence induce alteration in various tissues and cell types with impact on offspring phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The General Questionnaire is a Qualtrics-based tool filled in by a legal guardian that collects data on confounders, effect modifiers, and additional exposures. Some items were adopted from the existing studies (Dzhambov et al 2018a;Dzhambov et al 2018b;Heinrich et al 2017;Kuiper et al 2020), and some of the items were invented for the purpose of NeuroSmog. Briefly, information on socio-demographics, pregnancy and early life, general health, habits, academic performance, home, and neighbourhood environments of the child is being collected (see Supplement A for a paper-adopted version of the questionnaire).…”
Section: Study-specific Questionnairesmentioning
confidence: 99%
“…The results of cellular and animal models' studies support the notion that particulate and gaseous air pollutants generate reactive oxygen species, which results in oxidative stress and inflammatory responses 8 . The results of one recent study demonstrate that parental early-life exposure to particulate air pollution and ozone even in relatively clean Norway and Sweden increased the risk of asthma and hay fever in future offspring, which points out towards transgenerational effects of air pollution on allergy 9 .…”
Section: Introductionmentioning
confidence: 99%